2009
DOI: 10.1051/forest/2009027
|View full text |Cite
|
Sign up to set email alerts
|

Augmentation de la capacité photosynthétique avec l’altitude: mesures d’échanges gazeux à pressions partielles de CO2 ambiante et constante

Abstract: Abstract• Because all microclimatic variables change with elevation, it is difficult to compare plant performance and especially photosynthetic capacity at different elevations. Indeed, most previous studies investigated photosynthetic capacity of low-and high-elevation plants using constant temperature, humidity and light but varying CO 2 partial pressures (P CO2 ).• Using gas exchange measurements, we compared here maximum assimilation rates (A max ) at ambient and constant-low-elevation P CO2 for two temper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
13
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 42 publications
4
13
0
1
Order By: Relevance
“…Körner (2007) suggested that trees carry out a relatively high level of photosynthesis to compensate for extreme environmental conditions and short growing season at high altitudes. This hypothesis was confirmed also by Bresson et al (2009), who noted that the CO2 assimilation rate increased significantly with increasing altitude, approximately 2.8 µmol CO2 m -2 s -1 per 1000 m for beech. The small increase in maximum assimilation rate at high altitude may be attributed to a slight increase in stomatal conductance, implying an increase in CO2 diffusion into the leaf.…”
Section: Iforest -Biogeosciences and Forestrysupporting
confidence: 67%
See 2 more Smart Citations
“…Körner (2007) suggested that trees carry out a relatively high level of photosynthesis to compensate for extreme environmental conditions and short growing season at high altitudes. This hypothesis was confirmed also by Bresson et al (2009), who noted that the CO2 assimilation rate increased significantly with increasing altitude, approximately 2.8 µmol CO2 m -2 s -1 per 1000 m for beech. The small increase in maximum assimilation rate at high altitude may be attributed to a slight increase in stomatal conductance, implying an increase in CO2 diffusion into the leaf.…”
Section: Iforest -Biogeosciences and Forestrysupporting
confidence: 67%
“…Several studies reported changes in stomatal traits with increasing altitude in various plant species including beech; PCI, guard cell length or stomatal density were observed to increase with altitude (Hovenden & Brodribb 2000, Kouwenberg et al 2007, Bresson et al 2009, Paridari et al 2013, presumably compensating for a decrease of CO2 partial pressure, which limits photosynthetic potential across altitudinal gradients, shorter growing seasons and/or increasing UV radiation (Woodward & Bazzaz 1988, Kouwenberg et al 2007. The increase in stomatal density and index with altitude could be also result of opening up of the higher altitude landscape, which increases the amount of intercepted radiation (Hovenden & Brodribb 2000).…”
Section: Iforest -Biogeosciences and Forestrymentioning
confidence: 99%
See 1 more Smart Citation
“…Also, it was not possible to prove the effect of altitudinal gradients between the areas G1-G6 (750-1110 m a.s.l.) on P n , while, for example, Bresson et al (2009) …”
Section: Rate Of Photosynthesismentioning
confidence: 99%
“…Earlier plant physiological modelling studies concluded that the pressure reduction is largely mitigated by physical mechanisms such as faster molecular gas diffusion and parallel lowered O 2 , which competes with CO 2 at the Rubisco reaction site (Terashima et al, 1995). However, experimental investigations have shown that the photosynthetic capacity of upland population increases to the same extent as the partial CO 2 pressure is artificially raised (Körner and Diemer, 1987;Bresson et al, 2009). Transferred to the central Tibetan Plateau (w4500 m), this finding implies that alpine vegetation suffers from 40% lower carbon availability compared to sealevel.…”
Section: Changes In Atmospheric Co 2 Concentration As the Driving Formentioning
confidence: 99%